Phycobilisome protein ApcG interacts with PSII and regulates energy transfer in Synechocystis - Espinoza-Corral, Roberto; Iwai, Masakazu; Zavřel, Tomáš; Lechno-Yossef, Sigal; Sutter, Markus; Červený, Jan; Niyogi, Krishna K; Kerfeld, Cheryl A (Plant physiology, 2024)
Photosynthetic organisms harvest light using pigment-protein complexes. In cyanobacteria, these are water-soluble antennae known as phycobilisomes (PBSs). The light absorbed by PBS is transferred to the photosystems in the thylakoid membrane to drive photosynthesis. The energy transfer between these complexes implies that protein-protein interactions allow the association of PBS with the photosystems. However, the specific proteins involved in the interaction of PBS with the photosystems are not fully characterized. Here, we show in Synechocystis sp. PCC 6803 that the recently discovered PBS linker protein ApcG (sll1873) interacts specifically with PSII through its N-terminal region. Growth of cyanobacteria is impaired in apcG deletion strains under light-limiting conditions. Furthermore, complementation of these strains using a phospho-mimicking version of ApcG causes reduced growth under normal growth conditions. Interestingly, the interaction of ApcG with PSII is affected when a phospho-mimicking version of ApcG is used, targeting the positively charged residues interacting with the thylakoid membrane, suggesting a regulatory role mediated by phosphorylation of ApcG. Low-temperature fluorescence measurements showed decreased PSI fluorescence in apcG deletion and complementation strains. The PSI fluorescence was the lowest in the phospho-mimicking complementation strain, while the pull-down experiment showed no interaction of ApcG with PSI under any tested condition. Our results highlight the importance of ApcG for selectively directing energy harvested by the PBS and imply that the phosphorylation status of ApcG plays a role in regulating energy transfer from PSII to PSI.
Keywords: Phycobilisomes; Photosystem II Protein Complex; Energy Transfer; Synechocystis; Photosystem I Protein Complex; fykobilizomy; fotosystém I (proteinový komplex); fotosystém II (proteinový komplex); přenos energie